Sociodemographic and clinical profile of the elderly in Home Physiotherapy Programs - Barreto Grangeiro, Adriano Filipe; de Oliveira Gomes, Lucy; Elinor Alves Gama, Mônica; Franco Moraes, Clayton (O Mundo da Saúde, 2018)
The Brazilian population ages in an accelerated and progressive way. Evaluative studies that seek to trace the sociodemographic and clinical profile of the elderly in Home Physiotherapy programs of a given region is of great relevance as an indicator for the implementation of public and private services, avoiding unnecessary expenses, adequate resources and providing essential information for the direction of actions in home care. The objective of this research was to characterize the sociodemographic and clinical profile of the elderly people in home physiotherapy programs. This is an analytical study and cross-sectional design with elderly people from the public and private sectors using the Elderly Person's Health Handbook. The studied population was of 241 elderly with predominantly females in the two groups (average of 70.4%). The age ranged from 60 to 106 years, with a mean of 81.7 in the public sector and 82.5 in the private sector. Significant differences were found between the public and private service sector in the variables marital status (p<0.001), schooling (p<0.001), monthly income (p<0.001) and in the following diseases listed in ICD-10: Symptoms, signs and abnormal findings (p<0.001), Eye disease and (p<0.001), Nervous system disorders (p<0.001), Mental and behavioral disorders (p=0.032) and neoplasms (p=0.004). Evaluative studies in Home Physiotherapy Programs are fundamental, as it is possible to know the specificities of the elderly minimizing hospitalizations, reducing morbidity and mortality, minimizing functional disabilities providing continuous care in a dignified and humanized way guaranteeing increased longevity with quality of life.